Macronutrient intake in dyslipidemia: a population-based study from Haryana, North India - Yadav, Neha; Chaudhary, Vineet; Thakur, Mamta Kumari; Saraswathy, Kallur Nava; Devi, Naorem Kiranmala (International Journal of Research in Medical Sciences, 2023)
Background: Dyslipidemia is a highly prevalent physiological condition and it is one of the major risk factors for cardiovascular diseases (CVDs) worldwide. Diet as a modifiable factor gaining more scientific attention in managing the problem of dyslipidemia among vegetarian populations in order to reduce the burden of CVDs. Methods: The present study was conducted on a total of 497 adult participants of either sex recruited randomly from Palwal Haryana, North India. Data related to socio-demographic variables was collected by using pretested and modified interview schedules. Dietary data was collected by using validated food frequency questionnaire (FFQ), and entered and analyzed by using Dietcal software. Lipid profile was done on 12 hours overnight fasting blood samples by using commercial kits Randox, USA. All the statistical tests were performed by using IMB’s SPSS software version 22. Results: Adjusted odds ratio revealed that total fat intake was positively associated with TG and VLDL while carbohydrate intake was found to be positively associated with TG, low-HDL, LDL, and VLDL. >3 times intake of RDAs for total fats and carbohydrates posed 2.4 and 2-folds increased risk for high TG and VLDL. Conclusions: Present study suggested a positive association between the intake levels of macronutrients and elevated lipids. Nutritional education and promoting diet diversity among vegetarian populations may reduce the burden of dyslipidemia.